Genome-wide association analysis identifies a meningioma risk locus at 11p15.5. Issue 11 (12th May 2018) - Claus, Elizabeth B; Cornish, Alex J; Broderick, Peter; Schildkraut, Joellen M; Dobbins, Sara E; Holroyd, Amy; Calvocoressi, Lisa; Lu, Lingeng; Hansen, Helen M; Smirnov, Ivan; Walsh, Kyle M; Schramm, Johannes; et al.
Abstract: Background: Meningiomas are adult brain tumors originating in the meningeal coverings of the brain and spinal cord, with significant heritable basis. Genome-wide association studies (GWAS) have previously identified only a single risk locus for meningioma, at 10p12.31. Methods: To identify a susceptibility locus for meningioma, we conducted a meta-analysis of 2 GWAS, imputed using a merged reference panel from the 1000 Genomes Project and UK10K data, with validation in 2 independent sample series totaling 2138 cases and 12081 controls. Results: We identified a new susceptibility locus for meningioma at 11p15.5 (rs2686876, odds ratio = 1.44, P = 9.86 × 10 –9 ). A number of genes localize to the region of linkage disequilibrium encompassing rs2686876, including RIC8A, which plays a central role in the development of neural crest-derived structures, such as the meninges. Conclusions: This finding advances our understanding of the genetic basis of meningioma development and provides additional support for a polygenic model of meningioma.